Factors Affecting Quality of Health Care among Old Adults at Beni-Suef University Hospital (Medico Legal Update, 2021)
Background: Aging is the process of progressive change in the biological, psychological and social structureof individuals’. Quality is affected by both the technical performance of providers and the extent to which asystem reaches those in need.Aim of Study: The study aimed to assess the quality of health care delivered to old age and factors affectingquality of health care.Subjects and Method: The study was conducted in the inpatient units at Beni-Suef university hospital.Study sample were nurses and patients: For nurses; all nurses who have experience more than one year atmedical surgical department, urinary tract diseases, and provide care for geriatric patients was includedin this study. For patients; convenient sample from the pre mentioned setting. Two data collection toolswere used to carry out the current study namely; structured Interviewing questionnaire and observationalchecklists.Results: 26% of the nurses were satisfied according to work place satisfaction, the same was percentunsatisfied according to work place satisfaction, and the rest of them (48%) had average level of satisfaction.58% of nurses had unsatisfied level according to their performance. (42%) of participants had satisfied levelaccording to their performance.Conclusion and Recommendations: 38% of patients had fair level about their evaluation, 33% of them hadexcellent level about their evaluation to quality of health care, and 29% of them had average level and 41%of them had negative level of satisfaction. Periodic assessment of nurses› perception about quality of care ofelderly patient. Regular implementation of training programs regarding quality of care.